Understanding ageing : images, attitudes and proffessional practice - Biggs, Simon, 1955- (Buckingham ; Bristol, PA : Open University Press, 1993)
Outward understanding. Inward understanding. Body, time and image. Self-perception and older age. Intergenerational communication. Power and opperession. Older people and practitioners...
Keywords: Psychology; Old age; Aging -- Social aspects; Aging -- Psychological aspects